Transvalvular pressure gradients for different methods of mitral valve repair: only neochordoplasty achieves native valve gradients. (3rd October 2017) - Jahren, Silje Ekroll; Hurni, Samuel; Heinisch, Paul Philipp; Winkler, Bernhard; Obrist, Dominik; Carrel, Thierry; Weber, Alberto
Abstract: OBJECTIVES: Many surgical and interventional methods are available to restore patency for patients with degenerative severe mitral valve regurgitation. Leaflet resection and neochordoplasty, which both include ring annuloplasty, are the most frequently performed techniques for the repair of posterior mitral leaflet flail. It is unclear which technique results in the best haemodynamics. In this study, we investigated the effect of different mitral valve reconstruction techniques on mitral valve haemodynamics and diastolic transvalvular pressure gradient in an ex vivo porcine model. METHODS: Eight porcine mitral valves were tested under pulsatile flow conditions in an in vitro pulsatile flow loop for haemodynamic quantification. Severe acute posterior mitral leaflet flail was created by resecting the posterior marginal chorda. The acute mitral valve regurgitation was corrected using 4 different repair techniques, in each valve, in a strictly successive order: (i) neochordoplasty with polytetrafluoroethylene sutures alone and (ii) with ring annuloplasty, (iii) edge-to-edge repair and (iv) triangular leaflet resection, both with ring annuloplasty. Valve haemodynamics were measured and quantified for all valve configurations (native, rupture and each surgical reconstruction). The results were analysed using a validated statistical linear mixed model, and the P -values were calculated using a 2-sided Wald test. RESULTS: All surgical reconstruction techniques were able to sufficiently correct the acute mitral valve regurgitation. Neochordoplasty without ring annuloplasty was the only reconstruction technique that resulted in haemodynamic properties similar to the native mitral valve ( P -values from 0.071 to 0.901). The diastolic transvalvular gradient remained within the physiological range for all reconstructions but was significantly higher than in the native valve for neochordoplasty with ring annuloplasty ( P < 0.000), edge-to-edge repair ( P < 0.000) and leaflet resection ( P < 0.000). Neochordoplasty without ring annuloplasty resulted in a significantly better pressure gradient than neochordoplasty with a ring annuloplasty ( P < 0.000). Additionally, neochordoplasty with a ring annuloplasty resulted in significantly lower transvalvular pressure gradients than edge-to-edge repair ( P < 0.000) and leaflet resection ( P < 0.000). CONCLUSIONS: Neochordoplasty with or without ring annuloplasty was the reconstruction technique that almost achieved native physiological haemodynamics after repair of posterior mitral leaflet flail after acute isolated chordal rupture in our ex vivo porcine model.